2017
DOI: 10.1016/j.matbio.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics analysis of cartilage response to mechanical injury and cytokine treatment

Abstract: Mechanical damage at the time of joint injury and the ensuing inflammatory response associated with elevated levels of pro-inflammatory cytokines in the synovial fluid, are reported to contribute to the progression to osteoarthritis after injury. In this exploratory study, we used a targeted proteomics approach to follow the progression of matrix degradation in response to mechanical damage and cytokine treatment of human knee cartilage explants, and thereby to study potential molecular biomarkers. This proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Discovery experiments (nontargeted MS) were performed on a quadrupole Orbitrap benchtop mass spectrometer (Q Exactive) (Thermo Fisher Scientific, Waltham, WA) equipped with an EASY-nLC 1000 system (Thermo Scientific, Waltham, MA) as previously described ( 55 ). An MS scan [400 to 1200 mass/charge ratio ( m / z )] was recorded in the Orbitrap mass analyzer set at a resolution of 70,000 at 200 m / z , 1 × 10 6 automatic gain control target, and 100-ms maximum ion injection time.…”
Section: Methodsmentioning
confidence: 99%
“…Discovery experiments (nontargeted MS) were performed on a quadrupole Orbitrap benchtop mass spectrometer (Q Exactive) (Thermo Fisher Scientific, Waltham, WA) equipped with an EASY-nLC 1000 system (Thermo Scientific, Waltham, MA) as previously described ( 55 ). An MS scan [400 to 1200 mass/charge ratio ( m / z )] was recorded in the Orbitrap mass analyzer set at a resolution of 70,000 at 200 m / z , 1 × 10 6 automatic gain control target, and 100-ms maximum ion injection time.…”
Section: Methodsmentioning
confidence: 99%
“…which is based on guanidine hydrochloride. This method is not optimal for collagen extraction and depending on the extent of collagen cross-linking or subtypes in different samples, the results may vary 32 . It might therefore be premature to make any interpretation about collagens from our study, without further validation.…”
Section: Osteoarthritis Andcartilagementioning
confidence: 99%
“…Finally, the organic solvent concentration increased up to 90% in 5 min and kept at 90% for 7 min. The MS1 and MS2 scans were performed as previously described [ 14 ], with the exception of MS2 resolution that was set to 17,500 in this study. The system was controlled by Xcalibur™ Software (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…The raw DDA data were searched against the human Swiss-Prot database (Swiss-Prot_2015_06, containing 20,200 sequences) using Proteome Discoverer™ 2.1 Software (Thermo Fisher Scientific) as previously described [ 14 ], with the exceptions of included modifications, which in this study was: static modification: cysteine carbamidomethylation and dynamic modifications: N-terminal acetylation and methionine oxidation. In the data analysis, the top 3 peptides are averaged, which is based on a study that reported that the average MS signal response for the three most intense tryptic peptides signals per mole of protein is constant [ 15 ].…”
Section: Methodsmentioning
confidence: 99%